2008
DOI: 10.1089/tmj.2008.0102
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Intrabody Communication for Personal Healthcare Monitoring System

Abstract: In this paper we propose the use of intrabody communication (IBC) for a personal health monitoring system employing inexpensive, lightweight, miniature sensor platforms. Body area networks (BANs) with physiological sensors could improve current healthcare services and at the same time significantly reduce costs to public health systems. We are primarily looking to reduce the transmission power consumption of the wireless communication links by using very low power IBC to connect the BAN sensors, a change that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Other authors have studied the influence of electrode-skin contact. According to [141], the contact impedance between the electrode and the body is independent of the type of metal (aluminium, copper, bronze, brass, stainless steel, nickel silver, and silver/silver chloride (Ag/AgCl)). The results of Callejón et al [29] comparing different types of electrodes (pregelled Ag/AgCl, aluminium, and copper) confirmed that the electrode material does not bear too much influence on IBC performance whenever a conductor is used.…”
Section: Electrodes and Body Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other authors have studied the influence of electrode-skin contact. According to [141], the contact impedance between the electrode and the body is independent of the type of metal (aluminium, copper, bronze, brass, stainless steel, nickel silver, and silver/silver chloride (Ag/AgCl)). The results of Callejón et al [29] comparing different types of electrodes (pregelled Ag/AgCl, aluminium, and copper) confirmed that the electrode material does not bear too much influence on IBC performance whenever a conductor is used.…”
Section: Electrodes and Body Couplingmentioning
confidence: 99%
“…Alshehab et al [141] investigated the optimal configuration by considering inclusion and exclusion of a ground electrode touching the skin, different sizes of electrodes, ground circuit board, and the distance between the signal electrode and the circuit board. They concluded that the best configuration, in terms of the lowest path loss, was composed of only signal electrode touching the skin (round copper plate with 2-cm of diameter) and a 10-cm × 5-cm ground circuit board at a distance of 1.5-cm from the signal electrode.…”
Section: Electrodes and Body Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main problem in the design of a mobile health care system is the unit's power supply trying to accommodate the rapidly increasing performance of processors, memory and other components [1]. The lower power requirements of intra-body communication (IBC) as compared to near field electromagnetic waves, implies that it can be a suitable solution for Medical Body Area Networks (MBANs) in a mobile health care system [1].…”
Section: Introductionmentioning
confidence: 99%
“…Intra-body communication (IBC) in which the human body is used as a medium for signal transmission guide has attracted much attention in the study of Body Area Networks (BANs), because signals pass through the human body, electromagnetic noise and interference have little influence on transmissions [1] [2] [3].…”
Section: Introductionmentioning
confidence: 99%